2022
DOI: 10.1007/s10489-022-04293-7
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid static-sensory data modeling for prediction tasks in basic oxygen furnace process

Abstract: In this paper, we propose a novel data-driven prediction system for Multivariate Time Series (MTS) in an industrial context, where classic relational data contain key information in order to properly interpret the MTS. Particularly we focus on the accurate endpoint prediction of temperature and chemical composition at the basic oxygen furnace, which is a step in the steel production pipeline where liquid iron is refined to steel. The precise prediction of temperature is important for proper process control whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Additionally, with the growing environmental awareness of industrial processes, wastewater discharge and treatment in the petroleum and chemical industries have become crucial aspects worthy of attention. Stress-strain produced by steel heat Wang [11], He [12], Liu [13], Sala [14], Song [15],…”
Section: Review Of Dynamic Problems In Complex Industrial Processesmentioning
confidence: 99%
“…Additionally, with the growing environmental awareness of industrial processes, wastewater discharge and treatment in the petroleum and chemical industries have become crucial aspects worthy of attention. Stress-strain produced by steel heat Wang [11], He [12], Liu [13], Sala [14], Song [15],…”
Section: Review Of Dynamic Problems In Complex Industrial Processesmentioning
confidence: 99%
“…Figure 4 reveals that static features have been predominantly employed for BOF data‐driven modeling. Despite the significant role of process time‐series features, their availability has been limited to a few BOF datasets [26–28] . In Brämming et al., [29] a comprehensive blend of all available features—process parameters, image, off‐gas data, and vessel vibration audiometry measurements—was utilized to estimate foam height and endpoint phosphorus prediction.…”
Section: Data‐driven Modeling Workflow For Bof Processmentioning
confidence: 99%
“…The application of recurrent neural networks (RNNs), specifically long short‐term memory (LSTM), has been explored for handling time‐series data [53] . A deep learning framework based on fully connected networks (FCN) and CNN has been developed for regression tasks, taking into account both static and multivariate time series information [28] …”
Section: Data‐driven Modeling Workflow For Bof Processmentioning
confidence: 99%
“…For evaluation of the performance of the models, the metrics used are the root mean square error (RMSE) and the mean absolute percentage error (MAPE). RMSE is calculated as in Formula (13) and MAPE is calculated as in Formula (14).…”
Section: Model Evaluationmentioning
confidence: 99%
“…Figure 1 shows the result after searching the topic under study, which shows that the databases returned four articles in total. They focus on the following issues: hybrid static-sensory data modeling for prediction tasks in the basic oxygen furnace process [14]; temperature prediction for a reheating furnace by the closed recursive unit approach [15]; detecting and locating patterns in time series using machine learning [16]; and deep learning for blast furnaces [17]. Other studies found focus on steel forecasting in China [18], in Japan [19], and in Poland [20].…”
Section: Introductionmentioning
confidence: 99%